RAAS and stress markers in acute ischemic stroke: preliminary findings. (12th September 2014) - Back, C.; Thiesen, K. L.; Skovgaard, K.; Edvinsson, L.; Jensen, L. T.; Larsen, V. A.; Iversen, H. K.
<x xml:space="preserve">Abstract</x> Objectives Angiotensin II type 1 receptor blockade has neuroprotective effects in animal stroke models, but no effects in clinical stroke trials. We evaluated cerebral and peripheral changes in the renin angiotensin aldosterone system (RAAS) and stress responses in acute ischemic stroke patients. Materials and methods Blood from a jugular and cubital vein was collected within 48 h of stroke onset, after 24 and 48 h, and renin, angiotensin I, angiotensin II, aldosterone, norepinephrine, epinephrine, and cortisol were measured. Post‐stroke cubital vein samples were collected after 8 (4.7–10) months. Results The acute systolic blood pressure was significantly increased, 148 (141–168) vs 140 (130–147) mmHg post‐stroke. Angiotensin I, renin and aldosterone levels were significantly lower, angiotensin II was unchanged, and ACE activity was higher in the acute phase compared to post‐stroke. No differences in RAAS were detected between jugular and cubital plasma levels. Jugular venous plasma levels of epinephrine and cortisol were elevated in the acute phase compared to cubital levels (P < 0.05). Conclusion Increased epinephrine and cortisol levels in the jugular vein blood may reflect a higher peripheral turnover. The observed changes in RAAS in the acute stroke phase are consistent with responses to increased blood pressure.